Identification of Endoparasite in Feces of Cats (Felis catus) at APB Antasari Samarinda Clinic Using The Floating Method - Adinda Madhuri Hakim; Sari, Dewi Ratna; Jawa, Maria Elisabeth; Marthina; Anafi, Salshabilla Wahyu; Khatimah, Ardhiatul; Fitri Elizabrth Hasibuan; Hasibuan, Febry Rahmadhani (Journal of Parasite Science, 2025)
Parasites are organisms that rely on a host for survival and can be classified into ectoparasites, which live on the body surface, and endoparasites, which inhabit the internal organs. Transmission of gastrointestinal parasites in cats (Felis catus) occurs via eggs, cysts, or infective larvae present in contaminated soil, water, food, or feces. This study aimed to identify endoparasites in cat feces collected from the APB Antasari Samarinda Clinic using the floating method. Out of six fecal samples examined, two samples (33.3%) tested positive for endoparasitic infection: Ancylostoma spp. in Ciko and Toxocara spp. in Jamal. These results indicate that gastrointestinal parasites remain a significant health concern in domestic cats and may pose zoonotic risks to humans. The findings underscore the importance of routine deworming, proper hygiene management, and regular health monitoring of cats. Future research should increase sample size, employ molecular techniques for precise species identification, and explore environmental or seasonal factors influencing infection dynamics to better inform parasite control strategies.